Effectiveness Of Ultrasonic Pulse Velocity And Impact- Echo Ndt Techniques To Assess The Quality Of Concrete - Mohiuddin Khan, Shibli Russel (2002)
The deterioration of concrete in structure is a result of several internal or external degradation mechanism and which results in distress of the structure i.e. decrease in strength and integrity of the structure. The state of distress is often hidden from view and is only evident at a stage where there is significant reduction in strength of the structure. Defects are often introduced during construction and are viewed during in-service life. Some deterioration is viewed physically in the early age or during the service life of the structure in terms of spalling, surface crack, swelling and honeycombing. This deterioration collectively or individually results in reducing the load carrying capacity in terms of the distress of the structure. In this project, the common defects in the concrete structures and mapping techniques by nondestructive test are presented. Among the various techniques of the nondestructive tests, the Ultrasonic Pulse Velocity (UPV) and DOCtor's Impactecho were chosen for their effectiveness. The UPV is used to estimate the concrete strength, detecting flaws such as voids and cracks and also to investigate the effects of smaller diameter bar in the concrete. In detecting various sizes of voids by the Impact-echo test techniques a format was suggested to identify them from the frequency spectrum.